Neuromuscular and balance adaptations following basketball-specific training programs based on combined drop jump and multidirectional repeated sprint versus multidirectional plyometric training - Brini, S.; Boullosa, D.; Calleja-González, J.; Ramirez-Campillo, R.; Nobari, H.; Castagna, C.; Clemente, F. M.; Ardigò, L. P. (PLOS ONE, 2023)
Multidirectional jumping and repeated sprint ability are crucial performance factors in basketball. The main aim of this investigation was to examine the neuromuscular performance and body balance adaptations following basketball-specific combined training programs based on drop jump and multidirectional repeated sprint versus multidirectional plyometric training. Forty-two professional basketball male players participated in the current investigation and were randomly assigned to three groups: a combined group (COMB; n = 14), a multidirectional jump group (MJG; n = 14) and an active control group (CON; n = 14). The COMB and the MJG groups completed the 8-week training programs with two weekly sessions while the CON continued their usual training. The static and dynamic balance tests, the repeated sprint ability test (IRSA5COD), the T-change of direction (CoD) test, the vertical jump tests, the five time-jump test (FJT) were performed by participants before and after the intervention period. The results showed a significant main effect of time with remarkable improvements at the end of the intervention (P < 0.001, effect size small/moderate) except the physiological parameters for IRSA5COD. Only, significant group × time interactions for body balance, T-CoD test, IRSA5COD (total time and best time), and jump tests were found (P < 0.001, effect size from trivial to moderate). Bonferroni corrected post-hoc tests revealed significantly greater improvement in favor of COMB compared to MJG for body balance, CoD and IRSA5COD (P < 0.005, effect size small/moderate). Otherwise, no significant differences between COMB and MJG concerning jump performances were found. Combined drop jump and multidirectional repeated sprint training program lead to significantly better neuromuscular performance, body balance and CoD in professional basketball players when compared with an usual training.